A comprehensive management model to maximize the benefits of agriculture drainage water reuse. (27th March 2021) - Helal, Esam; Shaban, Mohamed; Abd El‐Karim, Ehab; Ellayen, Ashraf
Abstract: Water scarcity in Egypt is an escalating challenge due to the ever‐increasing water demands and limited resources. Economically, agricultural drainage water reuse (ADWR) in irrigation is an essential option to cope with freshwater shortage. However, it requires environmentally sound management to minimize possible risks on irrigated soils and human health. Consequently, this research aims at assessing and managing the reuse process by developing a statistically based quality control model capable to investigate the observed and expected capability of the process. Additionally, complementary corrective actions and the decision models were proposed when the reuse processes operate in violation of the standards. These models were tested and validated using data collected from the year 2015 to 2019 at the Delengat pump station in the Western Nile Delta region, which mixes the Delengat drain water with the El‐Hager irrigation canal. After raising the awareness amongst the farmers and providing them adequate sanitation services, it was inferred that the ADWR process could provide safe drainage water to be mixed with fresh water. Based on the performed simulations, both models proved to be systematic, quantitative, suitable for computers, and helpful in making informed decisions concerning the sustainability of the reuse process under future water uncertainty. Practitioner points: ▪ In Egypt, drainage water reuse is an essential option to cope freshwater shortage. ▪ A statistically based quality control model was developed to investigate the capability of the agriculture drainage water reuse process. ▪ Additionally, complementary corrective actions and decision models were proposed when the reuse processes operate in violation of the standards. ▪ Both the models proved helpful in making informed decisions concerning the sustainability of the reuse process under the future water uncertainty. Abstract : This figure shows the agricultural drainage water reuse management stages which comprise; Define and investigation of water quality problems, then water quality parameters measurements, after that analyze of data to determine problem solving mechanisms, then improving the quality of drainage water reuse, and finally drainage water reuse quality control stage.